Sistema de gestão ambiental aplicado a uma vinícola: um estudo de caso - Wendler, Daiana Fiorentin (2009)
This study aimed to propose an environmental management system for a Winery within the perspective of ISO 14001, as a situational diagnosis made in the company from November 2008 to May 2009. This is a case study, which used a qualitative approach. The media used were literature and field research. This work was characterized as descriptive and explanatory. The data for the study, were collected through primary sources (unstructured interview, questionnaire for the company s technical director, on-site observation) and secondary (company s legal documents and publications relevant to research). In order to confirm and validate the information provided, the researchers recorded photographic observations in the environment of the organization during the 2009 harvest and construction of flow charts of the processes of wine. The data collected and analized were showed scope for improvement through implementation of an environmental management system. It is based on a set of actions related to production processes of the organization and health management, safety and environmental protection. The study further demonstrates the importance of environmental management it s presented, a survey of environmental aspects and impacts provokated by the activities of the winery and actions that the company has been adopting for the beneficts of the environment. After this diagnosis, it was suggested an environmental policy with goals and targets for the winery. It is understood that the first step to implement a environmental management system in the company s awareness of the Executive Department of the importance of environmental issues. This proposed model is extended to other industries in the wine sector